Kualitas Mikrobiologi Udara Dan Identifikasi Jenis Mikroorganisme Pada Lantai Ruang Intensive Care Unit (ICU) Di Rumah Sakit Umum Daerah Dr. H. Abdoel Moeloek Bandar Lampung - Ayu Wulan Sari; Tri Umiana Soleha (CV. Jasa Sukses Abadi, 2020)
Nosocomial infection is an infection that is seen in a patient while in a hospital or other health facility, where the infection is not visible when a patient is admitted to the hospital. This research was conducted using descriptive observational laboratory methods. The study was conducted by taking air samples and wiping the floor to be planted on the media and viewed microscopically. To determine air quality and determine the type of microorganisms on the Intensive Care Unit (ICU) floor of the Regional General Hospital Dr. H. Abdul Moeloek Bandar Lampung. From the five points taken as a sample, the highest germ index was 244 CFU / m3. Gram-positive bacteria in the form of coccus are the most bacteria in the Gram staining of air samples. The growth of bacteria on the floor, which is Gram negative bacteria in the form of bacillus in all samples. The results of bacterial identification from biochemical tests showed a variety of bacteria. The quality of air microbiology in the Intensive Care Unit of the Regional General Hospital Dr. H. Abdul Moeloek Bandar Lampung is good with an average germ index of 153.4 CFU / m3.